Fundamentals of Entrepreneurship ENT300 : Zeus transportation and services / Muhamad Rafiq Jahangir ... [et al.] - Jahangir, Muhamad Rafiq; Empayie, Ritchie; Daniel, Fredy; Pengiran, Johannes; John, Johnston (2014)
Zeus Transportation and Services is a partnership company aimed to provide the customers with a comfortable car services .There are five (5) members of this company partnership which consist of the General Manager, Administration Manager, Operation Manager, Marketing Manager, and Financial Manager. The major objective of our company is to provide customers which mainly consist of UiTM and UNIMAS students in Kota Samarahan area. This will provide services that could help the students to move from one place to another with services that we provided with reasonable charges.